Characteristics and practices of “Christian-based” companies - Ibrahim, Nabil A. (Journal of business ethics, 1991)
There is a sizeable group of self-described “Christian” companies which have declared their belief in the successful merging of biblical principles with business activities. As these companies have become more visible, an increasing number of anecdotal newspaper and magazine articles about these companies have appeared. Surprisingly, no rigorous research has been conducted prior to our recent study. This article provides national estimates of the size and predominant characteristics of self-identified “Christian” companies. In addition, the study investigated the types of relationships these companies maintained with their employees, customers, communities, and suppliers.